La Cité de Dieu / Die Stadt Gottes - Hengel, Martin 1926-2009; Mittmann, Siegfried 1933-2022; Schwemer, Anna Maria 1942- (Mohr Siebeck, 2000)
This book is a collection of articles from a Tübingen symposium held by professors of the Universities of Strasbourg, Tübingen and Uppsala in 1998. This collection was preceded by the symposium volumes Le Trône de Dieu/Der Thron Gottes/The Throne of God (1993) and La Main de Dieu/Die Hand Gottes/The Hand of God (1997). The articles deal with the complex subject of The City of God from the aspects of the history of the Oriental, Hellenistic-Jewish and Islamic religions, biblical exegesis and patristics and of synagogal and Christian iconography